2021
DOI: 10.3390/genes12050727
|View full text |Cite
|
Sign up to set email alerts
|

The ATM Gene in Breast Cancer: Its Relevance in Clinical Practice

Abstract: Molecular alterations of the Ataxia-telangiectasia (AT) gene are frequently detected in breast cancer (BC), with an incidence ranging up to 40%. The mutated form, the Ataxia-telangiectasia mutated (ATM) gene, is involved in cell cycle control, apoptosis, oxidative stress, and telomere maintenance, and its role as a risk factor for cancer development is well established. Recent studies have confirmed that some variants of ATM are associated with an increased risk of BC development and a worse prognosis. Thus, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 74 publications
2
33
0
3
Order By: Relevance
“…A few previous studies have analyzed associations between the incidence of ATM variants and the frequency of contralateral breast cancer incidence after radiation therapy 51,52 . These studies suggest that some mutations in ATM may associate with a decreased risk of contralateral breast cancer recurrence 22 . Conversely, several studies have also identified that mutations in ATM may occur with higher frequency in metastatic breast cancer patients 53 .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…A few previous studies have analyzed associations between the incidence of ATM variants and the frequency of contralateral breast cancer incidence after radiation therapy 51,52 . These studies suggest that some mutations in ATM may associate with a decreased risk of contralateral breast cancer recurrence 22 . Conversely, several studies have also identified that mutations in ATM may occur with higher frequency in metastatic breast cancer patients 53 .…”
Section: Discussionmentioning
confidence: 89%
“…For instance, somatic inactivation of ATM/CHK2 signaling, through loss of upstream DNA repair pathways, induces resistance to endocrine therapy in ER+/HER2-breast cancer cells and patient tumors [17][18][19] . A role for germline variants in ATM/CHEK2 in ER+/HER2breast cancer initiation and outcomes has also been identified by large and multiple independent epidemiological studies [20][21][22][23] . Mutations in CHEK2 and ATM associate specifically with increased incidence of ER+/HER2-breast cancer that associates with worse survival outcomes 21,22,24 .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…While ATM has several tumor suppressing functions, ATM - induced signaling can cause tumor progression via the αvβ3 integrin pathway in some cancers ( 48 ). ATM-dependent signaling in tumor cells can also increase resistance to radiotherapy and chemoresistance ( 49 ). Due to its role in signaling pathways and DNA damage repair, ATM has been proposed as a potential target for the development of future chemotherapies ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound-guided sampling methods are usually minimally invasive techniques applied to obtain cytological specimens or tissue samples, mainly used for the diagnosis of different types of tumors, such as breast [ 1 ] and prostate cancers [ 2 ].…”
Section: Introductionmentioning
confidence: 99%